Cardiac allograft vasculopathy in Dutch heart transplant recipients - Galli, G. (Neth Heart J, 2016)
BACKGROUND: Cardiac allograft vasculopathy (CAV) is a multifactorial disease and a major cause of graft failure after heart transplantation. However, the impact of CAV may vary according to the definition and the regional differences in transplantation settings. OBJECTIVES: We sought to assess CAV prevalence, predictors and prognosis in Dutch heart transplant recipients based on coronary angiography, following the 2010 standard nomenclature of the International Society for Heart and Lung Transplantation. METHODS: Patients ≥18 years who underwent heart transplantation at our centre with at least one coronary angiography during follow-up were included in the analysis. Clinical variables were collected prospectively. RESULTS: Among 495 analysed recipients, there were 238 (48 %) with CAV. The prevalence of CAV was 18, 47 and 70 % at 4, 12 and 20 years, respectively. In the multivariable proportional hazards regression analysis, only male donor gender and increasing donor age were significantly associated with the risk of CAV. The long-term prognosis of the patients with CAV at fourth-year angiography was significantly worse as compared with that of CAV-free patients, independently of the severity of CAV (p < 0.001). CONCLUSION: The prevalence of CAV increased gradually over time, with a similar trend as in other registries. Post-transplant survival is decreased in patients with any degree of early CAV, indicating that management strategies should start with donor selection and preventive measures immediately after transplantation.